Prevention of wheezing episodes and asthma in high risk children with ketotifeno - Freyre Roman, Eleodoro (1992)
With the purpose to assess the prophylactic effectiveness of Ketotifen in the prevention of the development of wheezing episodes in non-asthmatic children clasified in a high-risk category according to a previousley prepared scale, two groups of 21 children, both similar with respect to age, sex and risk rating, were studied. The children of one group received ketotifen and those of the other group did not, both groups being followed during a 12-month period to estimate the development of wheeziness during that time.  The enviromental factors at home, such as the presence of smokers, pets, carpeted floors, and the number of siblings under 10 years of age, were similar in both groups.  A high correlation between the risk rating and the number of episodes of wheeziness in the group not treated with ketotifeno was encountered, thus confirming the value of the scale used.  In the group trated with ketotifen there was a significant lower number of children affected by wheeziness and also of the numer of wheezing episodes for the group as compared with the non-treated group. The differences became more obvious from the third mont of follow-up.  It is concluded that ketotifeno is effective in reducing the development of wheeziness in high-risk, non-asthmatic, and its use is recommended.